"All we Wanna do is be Free": Advocating for Black Liberation in and through K-12 Science Education. Issue 2 (17th February 2022) - Morton, Terrell R.; Miles, Monica L.; Roby, ReAnna S.; Ortiz, Nickolaus A.
ABSTRACT: This paper calls for a critical reimagination of science epistemology and praxis by advocating for a move toward Black liberation in and through K-12 science education. This call is driven by our desires as authors to foster a future of K-12 science teaching and learning that centers, embraces, and promotes historical and contemporary Black scientific innovation and creativity through practices that redress structural anti-Black racism and its implications on Black existence and life. Black Liberatory K-12 Science Education (BLKSE) names the existing challenges with cultivating and empowering Black minds in and through science as a result of anti-Black ideologies that ground and govern K-12 science access, teaching and learning. In naming said challenges as the manifestations of anti-Black ideologies, we shed light on the roles of K-12 science teachers and science teacher education regarding the treatment of Black students given oppressive policies and practices that fail to recognize Black brilliance and innovation. By advocating for a push toward BLKSE, we offer guiding concepts we feel are necessary to begin the process of rooting out anti-Blackness; a process that centers a holistic, heterogenous form of Blackness at the crux of science inquiry and understanding. As a result of this perspective, BLKSE embraces the beauty and creativity of Black youth, naming their positions and ideas as forms of scientific knowledge and inquiry, while disrupting existing mainstream paradigms and practices in science education. Implications for ways to work toward BLKSE in K-12 science teaching and teacher education are provided.